Socialization of Boat Hull Measurement Using Total Station to Traditional Boatbuilding Group in Tanah Beru, Bulukumba Regency - Sabaruddin Rahman; Daeng Paroka; Achmad Yasir Baeda; Chairul Paotonan; Hasdinar Umar; F.M. Assidiq (Faculty of Engineering UNHAS, 2022)
Wooden boat construction in a traditional boatbuilding group in Tanah Beru, Bulukumba district, continues to meet domestic and foreign orders. After construction, the craftsmen did not re-measure the hull so the boat’s characteristics were not well documented. This may be due to not being well understood how important these measurements are. This activity aims to introduce craftsmen to an easy way of measuring boat hull using a total station. The main dimensions of the boat that became the object of socialization were the deck length, breadth, and height of 37.75, 10.15, and 3.85 m, respectively. At the implementation stage, pre-test and post-test were conducted in the form of a questionnaire to determine the extent to which the program was successful. Among six participants of the socialization, there were two participants (33.33%) who understood the six definitions of the ship’s main dimension, namely the distance between perpendicular (LBP), length of waterline (L1), draft (T), deck length (L2 ), width of waterline (BWL) and overall width (B). While the other participants did not fully understand it. There was even one person who did not understand all of it. After socialization was carried out, 66.67% fully understood it. The measurement results show that the width and height of the built ship are 10.38 m and 4.00 m, respectively. These sizes are 0.20 and 0.15 m larger than the designed dimension.